A New Hypothesis Concerning the Big Bang - Negulescu, Vlad L. (Transactions on Engineering and Computing Sciences, 2024)
Using the fact that the power Pg is a tangent function, this paper develops a hypothesis concerning the beginning of the Universe and the Big Bang. Everything starts from an initial singularity which contains infinite power. Further the mass and the diameter of the whole Universe is also calculated.